The Importance Of Three-Stage Model In Developing The Functional Status Of Athletes - Sabirova Nasiba Rasulovna (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2021)
The problem of improving the effectiveness of the Athlete Training Management System is that all stages of the multi-year process of sports training are considered in terms of training tools and methods